A Perspective on the Lexicographic Value of Mega Newspaper Corpora — The Case of Afrikaans in South Africa - Prinsloo, D.J. (Lexikos, 2009)
Abstract: The aim of this article is to assess the potential use of a mega newspaper corpus, the Media24 archive, in the absence of large balanced and representative corpora, for the compilation of major general dic-tionaries for Afrikaans. Firstly, an evaluation of Media24 against the lemmalists of both a major single-vol-ume and a multi-volume monolingual dictionary for Afrikaans is undertaken to determine to what extent Media24 correlates with the lemmalists of major dictionaries. Secondly, the strength/suitability of Media24 for lemma selection in categories other than newspapers is evaluated. Finally, it is determined what the con-tribution could be of Media24 to lexical sense distinction, selection of examples of usage, and typical colloca-tions.Keywords: AFRIKAANS, MEDIA24 ARCHIVE, NEWSPAPER CORPORA, BALANCED CORPORA, REPRESENTATIVE CORPORA, WORD/LEXICOGRAPHIC/LEXICAL SENSE DIS-TINCTION, LEMMALIST, CORPUS DESIGNOpsomming: 'n Perspektief op die leksikografiese waarde van megakoe-rantkorpusse — Die geval van Afrikaans in Suid-Afrika. Die doel van hierdie arti-kel is om die bruikbaarheid van 'n megakoerantkorpus, die Media24-argief, te bepaal in die afwe-sigheid van groot, gebalanseerde en verteenwoordigende korpusse vir die samestelling van omvat-tende algemene woordeboeke vir Afrikaans. Eerstens word 'n evaluering van Media24 gedoen deur dit met die lemmalyste van 'n groot omvattende enkelvolume-, en 'n multivolumewoorde-boek van Afrikaans te vergelyk, ten einde te bepaal tot watter mate Media24 met die lemmalyste van groot woordeboeke korreleer. Tweedens word die gewig/toepaslikheid van Media24 vir lem-maseleksie uit kategorieë wat koerante uitsluit, geëvalueer. Ten slotte word bepaal wat die bydrae van Media24 kan wees tot leksikale betekenisonderskeiding, keuse van gebruiksvoorbeelde en tipiese kollokasies.Sleutelwoorde: AFRIKAANS, MEDIA24-ARGIEF, KOERANTKORPUSSE, GEBALAN-SEERDE KORPUSSE, VERTEENWOORDIGENDE KORPUSSE, WOORD/LEKSIKOGRAFIESE/ LEKSIKALE BETEKENISONDERSKEIDING, LEMMALYS, KORPUSONTWERP